Effect of sugarcane silage on productive parameters of replacement Holstein-Friesian heifers - José Reyes G (Revista MVZ Córdoba, 2014)
Objective. Measure the productive parameters of Holstein-Friesian females from weaning to 470 days old, comparing feeding through sugarcane silage (SCS) and corn silage (CS) in a concentrated fodder ratio of 70:30. Materials and methods. Twenty-eight post-weaning calves were used, with an average age of 80±16 days old and an initial weight of 79.5±12.9 kg. The T-Student test was used for the comparison of means, where calves were divided into two groups of 14, one for each treatment. The body weight BW (kg), wither height WH (cm), body condition BC (1 to 5 scale), daily weight gain DWG (kg) and feed conversion FC (kg) was measured every 30 days. Results. Differences were found between treatments, where heifers fed with SCS showed better BC (3.12), FC (7.4) as compared to the CS treatment. No significant differences were found in terms of DWG (0.666 and 0.743 kg/d). Conclusions. Feeding based on sugarcane silage allows for an improved body condition and feed conversion of animals having with this an acceptable and cost-effective production performance in the raising of dairy replacements.